The Modified Subcapital Metatarsal Osteotomy in the Treatment of Hallux Valgus Recurrence. Issue 5 (October 2020) - Scala, Andrea; Cipolla, Massimo; Giannini, Silvana; Oliva, Giulio
The purpose of the present study is to illustrate the use of a modified subcapital metatarsal osteotomy (MSMO) in the treatment of hallux valgus (HV) recurrence. The article reports the clinical and radiological outcomes of a cohort of 52 consecutive patients presenting with recurrent HV, treated with MSMO. A total of 52 patients (54 feet) underwent operations between May 2010 and November 2015. The mean time of follow-up was 2.5 years (range 5.5-1.0 years), and the mean age was 49 years (range 22-76 years). The patient cohort comprised 46 female and 6 male patients. The results of this research show that MSMO is a reliable technique for the correction of HV recurrence. The postoperative radiographic assessments show a statistically significant postoperative improvement of the HV angle (P < .05) and the intermetatarsal angle (P < .05). The postoperative position of the tibial sesamoid was significantly improved (P < .1). The distal metatarsal articular angle was improved (P < .001), though assessment may be affected by the previous operations performed on the first metatarsophalangeal joint. The statistical analysis shows that the postoperative American Orthopaedic Foot and Ankle Society Hallux Metatarsophalangeal-Interphalangeal Scale parameters were significantly improved (P < 0.001). Results of this study indicate that the minimally invasive MSMO is effective in restoring anatomical alignment and improving patient outcomes in recurrent cases of HV. Levels of Evidence: Level III: Case-control study